Stylistic analysis of the development of literary Persian and Turkish as seen in versions of Kalila Wa-Dimna, the Fables of Bidpay - Gehlhar, James Norman (The University of Edinburgh, 1976)
It has long been recognised that literary Persian and Turkish developed from stylistically simple beginnings and reached their zenith during the fifteenth and sixteenth centuries A.D., after which time both gradually became less ornate while maintaining many of the distinctive features of their Golden Age. This study, based upon a close reading of four Persian and four Turkish prose versions of Kalîla wa-Dimna, the fables of Bidpay, compares and contrasts each author's use of such rhetorical and stylistic elements as sac', simile, metaphor, narrative pace, arrangement of tales and inclusion of poetry, proverbs and religious quotations. By thus exploring in detail each writer's treatment of equivalent passages, this thesis for the first time enables us to draw specific conclusions about the stylistic development of the two literary languages and to pinpoint the influence exerted by Persian over Turkish.

The appendix to the thesis includes an edition of part of a hitherto unrecognised Persian translation of Abdullah b. al-Mukaffa''s Arabic Kalîla wa-Dimna. This unadorned Persian prose rendering by Mohammad b. 'Abdollah al-Bohari, dedicated to Sayf ad-Din Gazi b. 4Imâd ad-Din Zangi b. Ak Sonkor (541/1146- 544/1149) of Mosul, is a unicum dated Safar 544/June 1149, thus making it the earliest extant manuscript of Kalîla wa-Dimna in any of the Islamic languages, including Arabic. The work is, therefore, of great value as an example of early Persian provincial prose, as an indicator of the literary sophistication of the Atabeg court for whom it was written and as a potential means of more closely determining the nature of Ibn Mukaffa4's own text which has become seriously corrupted over the centuries